Kinerja Fitoremediasi Typha angustifolia L dalam Menurunkan Konsentrasi Timbal dan Tembaga di Sungai Silugonggo Juwana - Lestari, Safira Asanu; Ulfah, Maria; Dewi, Endah Rita Sulistiya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to evaluate the effectiveness of Typha angustifolia L. as a phytoremediation agent in reducing Pb and Cu concentrations in river water. The research employed a true experimental method using a completely randomized design with three biomass treatments (0 g, 80 g, and 160 g), each conducted in triplicate at two independently treated observation stations. The incubation period lasted seven days, during which metal concentrations were measured on days 0, 3, and 7 using atomic absorption spectrophotometry (AAS). The results demonstrated that the 160 g biomass treatment achieved the highest remediation efficiency. On day 7, Pb concentrations were reduced by 98.87% at Station 1 and 98.13% at Station 2, while Cu concentrations decreased by 91.76% and 94.88% at Stations 1 and 2, respectively. Statistical analysis using ANOVA followed by Tukey’s post hoc test indicated a significant effect of treatment on metal reduction (p < 0.05). It can be concluded that Typha angustifolia L. is effective as a phytoremediation agent, with remediation efficiency increasing with greater biomass and longer contact time, highlighting its potential application as an environmentally friendly solution for heavy metal pollution control.